Modeling of polycyclic aromatic hydrocarbons (PAHs) from global to regional scales: model development (IAP-AACM_PAH v1.0) and investigation of health risks in 2013 and 2018 in China - Z. Wu; Z. Wu; Z. Wu; X. Chen; X. Chen; X. Chen; Z. Wang; Z. Wang; Z. Wang; H. Chen; H. Chen; H. Chen; et al. (Geoscientific Model Development)
Polycyclic aromatic hydrocarbons (PAHs) significantly impact human health due to their persistence, toxicity, and potential carcinogenicity. Their global distribution and regional changes caused by emission changes, especially over areas in developing countries, remain to be understood along with their health impacts. This study implemented a PAH module in the global–regional nested Atmospheric Aerosol and Chemistry Model of the Institute of Atmospheric Physics (IAP-AACM) to investigate the global distribution of PAHs and the change in their health risks from 2013 to 2018 in China. An evaluation against observations showed that the model could capture well the spatial distribution and seasonal variation in Benzo[a]pyrene (BaP), the typical indicator species of PAHs. On a global scale, the annual mean concentrations are the highest in China followed by Europe and India, with high values exceeding the target values of 1 ng m−3 over some areas. Compared with 2013, the concentration of BaP in China decreased in 2018 due to emission reductions, whereas it increased in India and southern Africa. However, the decline is much smaller than for PM2.5 during the same period. The concentration of BaP decreased by 8.5 % in Beijing–Tianjin–Hebei (BTH) and 9.4 % in the Yangtze River Delta (YRD). It even increased over areas in the Sichuan Basin due to changes in meteorological conditions. The total incremental lifetime cancer risk (ILCR) posed by BaP only showed a slight decrease in 2018, and the population in east China still faced significant potential health risks. The results indicate that strict additional control measures should be taken to reduce the pollution and health risks of PAHs effectively. The study also highlights the importance of considering changes in meteorological conditions when evaluating emission changes from concentration monitoring.